Impact of Diet and Exercise Training‐Induced Weight Loss on Myocardial Mechanics in Severely Obese Adolescents. (5th October 2013) - Obert, Philippe; Gueugnon, Carine; Nottin, Stéphane; Vinet, Agnes; Gayrard, Sandrine; Rupp, Thomas; Dumoulin, Gilles; Tordi, Nicolas; Mougin, Fabienne
<x xml:space="preserve">Abstract</x> Objective Recent findings indicated silent incipient myocardial dysfunction in juvenile obesity despite normal global cardiac function. The present study investigated whether lifestyle intervention is able to favorably impact these obesity‐related myocardial abnormalities and whether improvements are related to changes in insulin resistance and cardiac remodeling. Design and Methods Twenty‐eight severe obese adolescents (OB) participated in a 9 month lifestyle intervention program (LIP) based on aerobic exercise and diet. Twenty healthy adolescents (CG) served as controls. Conventional echocardiography and myocardial mechanics were obtained at baseline and follow‐up along with insulin resistance. Results Insulin sensitivity improved (P < 0.001) and body weight decreased (P < 0.001) consecutive to LIP. At baseline, OB had depressed longitudinal (L) strain (CG: −18.3 ± 2.6, OB: −14.2 ± 3.6%, P < 0.001) and enhanced twist compared to controls. The LIP in OB restored L strain to normal values (−16.9 ± 3.5%, NS), whereas it did not affect twist mechanics. From stepwise multiple regression analysis, only baseline L strain and changes in BMI Z‐score (r2‐adjusted = 0.49, P < 0.001) emerged as independent predictors of L strain changes. Conclusions Juvenile obesity is associated with myocardial mechanic abnormalities that can be partly corrected by lifestyle intervention. Restoration of longitudinal myocardial function occurs in the absence of left ventricular remodeling changes and is not associated with insulin resistance improvements.